2014
DOI: 10.1508/cytologia.79.195
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Effects of Gamma Radiation and Its Impact on Growth and Yield of M1 and M2 Plants of Cowpea Cultivars

Abstract: SummaryThis study aimed at investigating the changes imposed by gamma radiation in mitotic activities and the chromosomes as well as the vegetative criteria and yield of M1 and M2 plants of five cowpea cultivars. Seeds of cultivars (Kaha 1, Dokki 331, Azmerly, Cream 7 and Giza 6) were exposed to levels of γ-radiation ranging from 50 to 300 Gy. Low levels of γ-radiation enhanced mitotic activity and resulted in significant increase in chromosomal abnormalities in the root tip cells of M1 and M2 plants. The perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
(15 reference statements)
6
19
0
Order By: Relevance
“…When the AgNPs concentrations were increased to 50 and 75 ppm, lower frequencies of chromosomal abnormalities were scored. Similar results were reported by Badr et al (2014) in cowpea root cells; a lower proportion of chromosomal abnormalities was scored as the γ-radiation dose increased.…”
Section: Cytological Effects Of Agnps: a Effect On Mitotic Indexsupporting
confidence: 85%
“…When the AgNPs concentrations were increased to 50 and 75 ppm, lower frequencies of chromosomal abnormalities were scored. Similar results were reported by Badr et al (2014) in cowpea root cells; a lower proportion of chromosomal abnormalities was scored as the γ-radiation dose increased.…”
Section: Cytological Effects Of Agnps: a Effect On Mitotic Indexsupporting
confidence: 85%
“…So, seedlings only survived for a maximum for two weeks. However, Badr et al (2014) found that 300 Gy was the toxic dose in cowpea while Horn and Shimelis (2013) showed toxic doses greater than 400 or 600 Gy depending on cowpea genotypes. These results differ from those of Essel et al (2016) which showed no significant effect of increasing doses of gamma irradiation on cowpea germination.…”
Section: Effect Of γ-Radiation On Cowpea Germination and Seedling Surmentioning
confidence: 98%
“…Kaha 1 and var. Dokki 331 Cowpea compared to other varieties, as estimated by the cluster analysis of seed protein, RAPD and ISSR markers 29 . In the same concern Žiarovská et al 30 indicated that the different ISSR fingerprint patterns of the amaranth mutant lines when compared to the Ficha cultivar and K-433 hybrid, ISSR specific profiles may be part of a consequence of the complex response of the intergenic space of mutant lines to the gamma-radiance.…”
Section: Primer Namementioning
confidence: 99%
“…Disappearance of ISSR bands in some M 1 and M 2 plants could be referred to damages of DNA like single or double-strand breaks, modified bases, oxidized bases, and bulky adducts. In addition, DNA-protein crosses links, point mutations and rearrangement of chromosomes were induced by gamma irradiation 29 . Furthermore, it has been shown that free radicals interact with biomolecules as DNA and remove electrons from them, so they www.scienceasia.org damage both structure and activity of the DNA.…”
Section: Primer Namementioning
confidence: 99%